Pengaruh Game Pembelajaran Bahasa Arab sebagai Sarana Pembelajaran Jarak Jauh - Agus Yasin; Achmad Farouq Abdullah; Audria Neviezka Sarasti Syafrodin (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research departs from the basic problem of declining student achievement at MI Nurussalam Dadung in Arabic lessons. During the pandemic, the learning process was carried out only by distributing lessons via WhatsApp without face-to-face meetings. Learning Arabic must be done directly so that students fully understand the sound, writing, and meaning of words. Because of this, there was a decrease in students' abilities, especially in Arabic lessons after the implementation of the distance learning system. Then, the researcher is interested in studying the use of learning games to assist the learning process when the distance learning system is implemented. This study aims to determine the effect of Arabic learning games on distance education. This research is based on the premise that the use of learning media can improve students' abilities in learning Arabic during the distance learning process. The results of this study are that the use of Arabic learning games is effective in developing students' abilities in Arabic lessons during distance learning but at a low level of effectiveness. In addition, learning media in the form of learning games also have a positive influence on students and teachers in the learning process, especially in distance learning. Keywords: Instructional Media; Arabic Learning Game; Distance Learning